Characterization and comparison of gasification and incineration fly ashes generated from municipal solid waste in Singapore - Qin, Junde (2022)
Slagging-gasification has received increasing attention as a municipal solid waste treatment technology. Compared with incineration, slagging-gasification can produce valuable syngas and generates by-products that can be easier reusable in different applications in some cases. Among these by-products, the gasification fly ash (GFA) is the only hazardous solid residue to be landfilled. To explore its potential recycling methods and maximize its recycling efficiency, the detailed physicochemical properties of GFA are crucial. This study conducted a comprehensive characterization of six GFA samples and the results were compared with one incineration fly ash (IFA) sample and available data of IFA collected in Singapore in literature. X-ray fluorescence (XRF), and microwave acid digestion (MAD) followed by inductively coupled plasma optical emission spectroscopy (ICP-OES) and inductively coupled plasma mass spectroscopy (ICP-MS) were carried out to determine the physicochemical composition of ashes. X-ray diffraction (XRD) and thermogravimetric analysis (TGA) were applied to identify their mineralogical composition. The hazard of the material was assessed through one-stage batch leaching tests. The results showed that the GFAs and IFA were both mainly composed of calcium compounds and chloride salts. However, GFA contained higher amounts of heavy metals especially lead (Pb) and zinc (Zn) than IFA. Zn contents in tested GFA samples were in a range of 1.4-3.0%, indicating the potential to recover Zn. The Ca(OH)2 content in GFA samples was up to 24.1%, which could be recovered as a low-grade lime. Based on the characteristics of GFA, a reusing method combining civil engineering utilization and resource recovery was suggested.